2015
DOI: 10.1098/rsif.2014.0893
|View full text |Cite
|
Sign up to set email alerts
|

Social information use and the evolution of unresponsiveness in collective systems

Abstract: Animal groups in nature often display an enhanced collective informationprocessing capacity. It has been speculated that natural selection will tune this response to be optimal, ensuring that the group is reactive while also being robust to noise. Here, we show that this is unlikely to be the case. By using a simple model of decision-making in a dynamic environment, we find that when individuals behave rationally and are subject to selection based on their accuracy, optimality of collective decision-making is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 52 publications
3
39
0
1
Order By: Relevance
“…Moreover, modeling selection on individual decision making in dynamic environments revealed that individuals that behave rationally based on all available information generally do not reach optimal decision-making. Instead, evolved individuals become overly reliant on social information, exhibiting delayed responses to environmental change, followed by rapid compensatory reactions that drive costly population volatility [81]. These dramatic reactions result from information cascades, in which individuals copy the behaviors of others that, themselves, are often simply copying the behaviors of others[ 2 9 7 _ T D $ D I F F ] , as opposed to making decisions based on direct interactions with their environment.…”
Section: Social Information and Ecology In A Changing Worldmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, modeling selection on individual decision making in dynamic environments revealed that individuals that behave rationally based on all available information generally do not reach optimal decision-making. Instead, evolved individuals become overly reliant on social information, exhibiting delayed responses to environmental change, followed by rapid compensatory reactions that drive costly population volatility [81]. These dramatic reactions result from information cascades, in which individuals copy the behaviors of others that, themselves, are often simply copying the behaviors of others[ 2 9 7 _ T D $ D I F F ] , as opposed to making decisions based on direct interactions with their environment.…”
Section: Social Information and Ecology In A Changing Worldmentioning
confidence: 99%
“…Computational models have shown that social information can improve the ability of groups of foragers to track resources that shift at small spatial scales and over relatively short, behavioral timescales [5,9,79] or between breeding seasons [32], but that large-scale or longterm environmental changes can eliminate these benefits or cause social information to become highly detrimental to populations [32,80,81]. For example, habitat fragmentation can reduce or cease migration in populations that rely on information from a small number of leaders, the leadership by which can fail to evolve in a fragmented landscape [ 2 9 6 _ T D $ D I F F ] [80].…”
Section: Social Information and Ecology In A Changing Worldmentioning
confidence: 99%
“…Specifically, when the environmental cue is about predators, the strategy being used by the majority sets a social context that can prevent other strategies from invading. Conversely, Torney et al (2015) found that an individual using a high amount of social information can do well when that is the minority strategy. Frequency dependence seems to be a common property of systems in which animals use social information (Rieucau and Giraldeau 2011).…”
Section: Discussionmentioning
confidence: 93%
“…While there are many models of the evolution of social-information use, few, to our knowledge, compare information about different facets of the environment (in our case, predators and resources). Additionally, while some models of the evolution of social-information use consider the weight given to social information (as opposed to personal information) (e.g., Pais and Leonard 2014;Shaw and Couzin 2013;Torney et al 2015), none to our knowledge consider the evolution of the number of neighbors in a topological interaction network. Finally, our work considers two group-level properties that have not previously been studied together.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional research suggests that schooling has many aspects of benefits, such as improvements of navigational performance (Berdahl et al 2014;Torney et al 2015), hearing perception (Larsson 2009(Larsson , 2012, and foraging efficiency (Di-Poi et al 2014;Wang et al 2016). These benefits are modelled in a lumped manner as…”
Section: Objective Functionmentioning
confidence: 99%